Pharmacological treatment of Parkinson’s disease - Michałowska, Małgorzata (Przewodnik Lekarza/Guide for GPs, 2009)
The treatment of Parkinson’s disease is a symptomatical management of both motor as well as many nonmotor features appearing in the course of the disease. The pharmacological choice is often challenging. An individual approach is required because of the changing clinical situation and the need of evaluation of benefit and risk of adverse effects. Principles of the pharmacological treatment were presented in the article. Emphasis has been placed on controversies about the initial treatment, the prevention of motor complications and the clinical consequence of dyskinesias.